A career in neurosurgery: perceptions and the impact of a national SBNS/NANSIG neurosurgery careers day. (3rd September 2022) - Solomou, Georgios; Venkatesh, Ashwin; Patel, Waqqas; Chari, Aswin; Mohan, Midhun; Bandyopadhyay, Soham; Gillespie, Conor S.; Mendoza, Nigel; Watts, Colin; Jenkins, Alistair; ,
Abstract: Objective: Entrance to neurosurgical training is highly competitive. Without proper advice, information and opportunities, talented individuals may be dissuaded from applying. The Neurology and Neurosurgery Interest Group (NANSIG) organises a Careers Day in Neurosurgery every year. Our objective was to assess the overall utility of a neurosurgery careers day and the perceived factors that attract and detract from the specialty, from attendees of the ninth annual neurosurgery careers day. Methods: Eighteen-item pre-conference and 19-item post-conference questionnaires were disseminated electronically to conference attendees. Questions aimed to capture: (i) baseline demographics; (ii) previous experience and exposure in neurosurgery; (iii) interest in neurosurgery; (iv) understanding training and a career in neurosurgery; (v) perceived factors of attraction and dissuasion of neurosurgery; and (vi) perceived value, quality and educational purpose of the conference. Results: In total, 77 delegates attended the careers day. Most did not have a formal neurosurgical rotation during medical school (24.7%, n = 19), but almost half had gained neurosurgical experience and presented research work. The careers day increased knowledge of the neurosurgical application process (median Likert score 3/5 to 4/5, p < 0.01), duration of training (72.7–88.3%), and desire to pursue a career in neurosurgery (75.3–81.8%). The most commonly reported factors attracting delegates to neurosurgery were interest in neuroanatomy (80.5%, n = 62), practical skills (64.9%, n = 50), and impact on patients (62.3%, n = 48). The most common dissuasive factors were competition to entry (64.9%, n = 50), long working hours (40.3%, n = 31), and other career interests (35.1%, n = 27). Almost all would recommend the event to a colleague (94.9%, n = 73). Conclusions: Formal undergraduate exposure to neurosurgery is limited. Neurosurgery careers days increase awareness and understanding of the application process and improve interest in a selected cohort. The factors attracting applicants to neurosurgery remain practical links to neuroanatomy, opportunities in neurosurgery for innovation and research, and direct impact on patients.